PENERAPAN METODE ACTIVITY BASED COSTING DALAM PENETAPAN HARGA JUAL PRODUK - Monicha Safira Chaerunisa; Aladin Aladin; Sarikadarwati Sarikadarwati (Politeknik Negeri Sriwijaya, 2021)
In determining the selling price of each product, the FAR Interest Depot only based on a certain estimated price without any calculation regarding the difference between the selling price and the cost of goods. The purpose of this study is to calculate the cost of goods manufactured accurately by using the Activity Based Costing (ABC) method to determine and determine the optimal profit in each product sale. The application of ABC for calculating the cost of production in determining the selling price, especially for Compost Fertilizer and Cement Flower Pot products. The data used in the form of primary data and secondary data. Data collected by means of observation and interviews. By using ABC, the calculation results obtained are more accurate because they include all types of variables in determining the cost of production so that it is expected that the profit that can be generated from production is maximized